Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.